Group choices seemingly at odds with individual preferences. Issue 7 (19th July 2017) - Laurent Salazar, Michel-Olivier; Nicolis, Stamatios C.; Calvo Martín, Mariano; Sempo, Grégory; Deneubourg, Jean-Louis; Planas-Sitjà, Isaac
Abstract : Numerous studies have focused on the influence of the social environment and the interactions between individuals on the collective decision-making of groups. They showed, for example, that attraction between individuals is at the origin of an amplification of individual preferences. These preferences may concern various environmental cues such as biomolecules that convey information about the environment such as vanillin, which, for some insects, is an attractant. In this study, we analysed how the social context of the cockroaches of the species Periplaneta americana modifies preferences when individuals are offered two shelters, of which one is vanillin scented. One of the principal results of our study is that isolated individuals stay longer and more frequently in a vanillin-scented shelter, while groups choose more frequently the unscented one. Moreover, the proportion of sheltered insects is larger when the group selects the unscented shelter. Our experimental results and theoretical model suggest that the individual preference is not inverted when insects are in a group but, rather, the response to vanillin decreases the attraction between individuals. As a result, aggregation is favoured in the unscented shelter, leading therefore to a collective inversion.